STOCK INVENTORY INFORMATION SYSTEM AT AHASS DEALER ASTRA MOTOR BASED ON WEB & MYSQL USING WEIGHT MOVING AVERAGE METHOD - Yopi Mahendra Mahendra (International Journal Cister, 2022)
Astra Motor's address is at Jl. A. Yani 99 Sumatra South of Palembang City is a dealer engaged in the sale and service of bicycles motorcycles and other motorcycle accessories and is a distributor who sells low prices so that many customers and agents buy goods at Ahass. processing data compared with information that is still using the manual system or not fully using the system computerized. Still using the sales receipt and then handed it over to the section sales records to be recorded into Microsoft Excel which which in the recording is less attractive and inefficient, so that the data it only displays sales data such as reports that sometimes quite hampered, in the presentation of the report given at the end of the month which is not yet possible to be accessed at any time and also happens delay in reporting sales information therefore, the occurrence of delays in a reporting process, namely one to one two days the same thing at the Ahass Astra Motor dealer. Often encountered by customers very disappointed because the stock of the item you want to buy doesn't exist and has run out but they've come to the dealer directly by wasting time or less efficient, either for own use or for resale. Ahass Adiba This is only specifically for selling and if consumers come directly to the dealer they can get it install the parts and accessories of the motorbikes that have been purchased, Ahass Astra Motor it supplies it from Palembang and outside Palembang.